2023
DOI: 10.3389/fendo.2023.1050049
|View full text |Cite
|
Sign up to set email alerts
|

Identification of shared genetic architecture between non-alcoholic fatty liver disease and type 2 diabetes: A genome-wide analysis

Abstract: BackgroundThe incidence of complications of non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D) has been increasing.MethodIn order to identify the shared genetic architecture of the two disease phenotypes of NAFLD and T2D, a European population-based GWAS summary and a cross-trait meta-analysis was used to identify significant shared genes for NAFLD and T2D. The enrichment of shared genes was then determined through the use of functional enrichment analysis to investigate the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Epidemiological data has revealed that the age-adjusted risk of NAFLD is approximately 5.36 times greater in individuals with T2DM as opposed to the general non-diabetic population (45). Prior MR studies also presented evidence supporting correlations between genetic predisposition to T2DM and an escalated risk of NAFLD, particularly within European populations (46). These findings align with our MR analysis, albeit our study was conducted on a larger sample size.…”
Section: Discussionsupporting
confidence: 89%
“…Epidemiological data has revealed that the age-adjusted risk of NAFLD is approximately 5.36 times greater in individuals with T2DM as opposed to the general non-diabetic population (45). Prior MR studies also presented evidence supporting correlations between genetic predisposition to T2DM and an escalated risk of NAFLD, particularly within European populations (46). These findings align with our MR analysis, albeit our study was conducted on a larger sample size.…”
Section: Discussionsupporting
confidence: 89%
“…proposed the concept of Hepatic Diabetes (HD) in 1967, pointing out that patients with chronic liver disease are more likely to have impaired glucose tolerance and complicated diabetes ( 22 ). Although some researchers have studied the relationship between DM and liver disease, the majority of studies have solely focused on non-alcoholic fatty liver disease ( 23 , 24 ), and little information is available on the potential relationship between DM and PBC risk. Meanwhile, previous findings in the literature were limited to observing correlations, and reverse causality may not be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Tan et al carried out the MR study to demonstrate a positive causal correlation between T2D and NAFLD. 19 Ruth et al also demonstrated a negative correlation between SHBG levels in serum and the risk of T2D using MR analysis, suggesting that a decrease in SHBG levels in serum would elevate the risk of developing T2D. 20 Based on this, we employed a two-sample MR approach to explore the causal relationship between SHBG and NAFLD.…”
Section: Introductionmentioning
confidence: 95%
“…Previously published MR studies have reported that free thyroid hormone levels, vitamin D levels and plasma phospholipid arachidonic acid levels in serum are all causally associated with the risk of NAFLD 16–18 . Tan et al carried out the MR study to demonstrate a positive causal correlation between T2D and NAFLD 19 . Ruth et al also demonstrated a negative correlation between SHBG levels in serum and the risk of T2D using MR analysis, suggesting that a decrease in SHBG levels in serum would elevate the risk of developing T2D 20 .…”
Section: Introductionmentioning
confidence: 99%